Human Resource Planning in Improving The Quality of Education at State Middle School 25 Tangerang - Ulul Azmi Ulul; Hermawan Hermawan; Mahdi Mahdi; Muhammad Mahen (UIN Siber Syekh Nurjati Cirebon, 2025)
Human resources have an important role in realizing the goals of educational institutions, so human resource planning must be carried out properly by the leadership so that the human resources in educational institutions can work optimally. The purpose of this study is to describe human resource planning, educational quality, and human resource planning in improving the quality of education at SMPN 25 Tangerang. The approaches and methods in this study used descriptive qualitative. Research data collection techniques were carried out through interviews, observation, and document studies. The results of this study describe human resource planning at SMPN 25 Tangerang by paying full attention to the specifications and criteria in terms of the character and performance of teachers and their employees. Steps taken by the school by forming a School Development Team. Schools try to maintain and improve school quality standards by providing quality education. In addition, education quality assurance is carried out through accreditation, internal evaluation, external evaluation, student assessment, regular monitoring and feedback. As for Human Resources planning in improving the quality of education at SMPN 25 Tangerang by maximizing the standards of educators and educational staff, so that the competence and qualifications of educators and educational staff can be maximized. Keywords : Planning, Human Resources, Quality of Education, National Education Standards